Physical activity combined with resistance training reduces symptoms of frailty in older adults: A randomized controlled trial. (May 2018) - Nagai, Koutatsu; Miyamato, Toshiaki; Okamae, Akio; Tamaki, Akira; Fujioka, Hiroyuki; Wada, Yosuke; Uchiyama, Yuki; Shinmura, Ken; Domen, Kazuhisa
Highlights: Physical activity intervention is feasible even in older adults with frailty symptoms. The intervention can increase the number of daily steps and engagement in low-intensity PA. Physical activity with RT can reduce frailty symptoms. Abstract: Introduction: Increased physical activity (PA) is a crucial factor in the prevention of physical deterioration, and resistance training (RT) is also a common and effective intervention for older adults. However, the effects of PA as an adjunct to RT on frailty status remains unclear; therefore, we clarified the effect of a PA intervention with feedback, as an adjunct to resistance strength training, on the physical and mental outcomes of frail older adults. Materials and methods: We employed a randomized controlled trial. Community-dwelling frail older adults in Japan were recruited to participate. Forty-one participants (mean age 81.5) were randomly assigned to engage in a resistance training with PA (RPA group) or RT group for six months. Frailty status and frailty scores, which were measured according to the Cardiovascular Health Study criteria—muscle strength, mobility, instrumental activities of daily living, and health-related quality of life—were assessed. Results: Participants in the RPA group exhibited a significant increase in light-intensity PA, the number of steps taken daily (p < 0.05), and lower-limb muscle strength (p < 0.05) and a significant decrease in frailty scores. However, pre- and postintervention frailty status, instrumental activities of daily living, and health-related quality of life did not differ significantly. Conclusions: Implementation of a PA intervention as an adjunct to RT is feasible, as it reduced frailty scores and increased lower-limb muscle strength and mobility in older adults with frailty symptoms.